Inhibition of acetylcholinesterase and butyrylcholinesterase by a plant secondary metabolite boldine - Kostelník, Adam; Pohanka, Miroslav (My University, 2018)
Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) are two enzymes sensitive to various chemical compounds having ability to bind to crucial parts of these enzymes. Boldine is a natural alkaloid and it was mentioned in some older works that it can inhibit some kinds ofAChE.We reinvestigated this effect onAChE and also on BChE using acetyl (butyryl) thiocholine and Ellman’s reagents as standard substances for spectrophotometric assay.We found out IC50 of AChE equal to 372 𝜇mol/l and a similar level to BChE, 321 𝜇mol/l.We conclude our experiment by a finding that boldine is cholinesterase inhibitor; however we report significantly weaker inhibition than that suggested in literature. Likewise, we tried to investigate the mechanism of inhibition and completed it with in silico study. Potential toxic effect on cholinesterases in real conditions is also discussed.
Inhibiční studie boldinu na acetylcholinesterasu a butyrylcholinesterasu
Keywords: Acetylcholinesterase; butyrylcholinesterase; inhibition; docking; boldine; Acetylcholinesterasa; butyrylcholinesterasa; inhibice; dokování; boldin